Numerical investigation of heat transfer in parallel channels with water at supercritical pressure - Edward Shitsi; Seth Kofi Debrah; Vincent Yao Agbodemegbe; Emmanuel Ampomah-Amoako (Heliyon, 2017)
Thermal phenomena such as heat transfer enhancement, heat transfer deterioration, and flow instability observed at supercritical pressures as a result of fluid property variations have the potential to affect the safety of design and operation of Supercritical Water-cooled Reactor SCWR, and also challenge the capabilities of both heat transfer correlations and Computational Fluid Dynamics CFD physical models. These phenomena observed at supercritical pressures need to be thoroughly investigated.An experimental study was carried out by Xi to investigate flow instability in parallel channels at supercritical pressures under different mass flow rates, pressures, and axial power shapes. Experimental data on flow instability at inlet of the heated channels were obtained but no heat transfer data along the axial length was obtained. This numerical study used 3D numerical tool STAR-CCM+ to investigate heat transfer at supercritical pressures along the axial lengths of the parallel channels with water ahead of experimental data. Homogeneous axial power shape HAPS was adopted and the heating powers adopted in this work were below the experimental threshold heating powers obtained for HAPS by Xi. The results show that the Fluid Centre-line Temperature FCLT increased linearly below and above the PCT region, but flattened at the PCT region for all the system parameters considered. The inlet temperature, heating power, pressure, gravity and mass flow rate have effects on WT (wall temperature) values in the NHT (normal heat transfer), EHT (enhanced heat transfer), DHT (deteriorated heat transfer) and recovery from DHT regions. While variation of all other system parameters in the EHT and PCT regions showed no significant difference in the WT and FCLT values respectively, the WT and FCLT values respectively increased with pressure in these regions. For most of the system parameters considered, the FCLT and WT values obtained in the two channels were nearly the same. The numerical study was not quantitatively compared with experimental data along the axial lengths of the parallel channels, but it was observed that the numerical tool STAR-CCM+ adopted was able to capture the trends for NHT, EHT, DHT and recovery from DHT regions. The heating powers used for the various simulations were below the experimentally observed threshold heating powers, but heat transfer deterioration HTD was observed, confirming the previous finding that HTD could occur before the occurrence of unstable behavior at supercritical pressures. For purposes of comparing the results of numerical simulations with experimental data, the heat transfer data on temperature oscillations obtained at the outlet of the heated channels and instability boundary results obtained at the inlet of the heated channels were compared. The numerical results obtained quite well agree with the experimental data. This work calls for provision of experimental data on heat transfer in parallel channels at supercritical pressures for validation of similar numerical studies.